Specific gut microbiota and serum metabolite changes in patients with osteoarthritis - Wang, Wendong; Liu, Xincheng; Nan, Hao; Li, Huan; Yan, Litao (Frontiers in Cell and Developmental Biology, 2025)
IntroductionRecent research indicated a strong link between the gut microbiota and osteoarthritis. However, the complex interplay between the gut microbiota, serum metabolites, and the progression of osteoarthritis in affected individuals remains largely unexplored. This study aimed to investigate the characteristics of the gut microbiota and serum metabolites in patients with osteoarthritis.MethodsParticipants with either healthy knees or osteoarthritis were enrolled and categorized into healthy control (HC) and osteoarthritis (OA) groups. Fecal and blood samples were collected for 16S rRNA gene sequencing, metabolomic analysis via liquid chromatography–mass spectrometry (LC-MS), and integrated evaluation.ResultsThe results showed no significant variation in gut microbiota richness and diversity between the two groups. However, the abundance of Bacteroides plebeius and Faecalibacterium prausnitzii was reduced in the OA group, both of which are known for their potential as next-generation probiotics for human health. Metabolomic analysis indicated that serum metabolites, including pyrogallol and 3-hydroxybutyrate (3HB), were significantly lower in the OA group. These metabolites are known to positively impact osteoarthritis progression and other diseases and demonstrated good diagnostic performance for distinguishing osteoarthritis patients from healthy controls. Correlation analysis revealed a positive correlation between Bacteroides plebeius and Faecalibacterium prausnitzii and between pyrogallol and 3HB.DiscussionThis study highlighted specific gut microbiota and serum metabolite profiles in osteoarthritis patients, suggesting that the specific changes in bacteria and derived metabolites are closely tied to osteoarthritis progression. This underscores the potential of gut microbiota and serum metabolites as modifiable elements and therapeutic targets for osteoarthritis prevention.